ANALISIS PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN NON DOSEN PADA UNIVERSITAS MERCU BUANA JAKARTA - Anwar Ikhsan (Universitas Mercu Buana, 2016)
The objective of this research is to analyze the effect culture organization, employee’s satisfaction to thestaff performance in Unviersity of Mercu Buana Jakarta, The Research use the approach of survey methodand then analyzed using regresion partial and simultan.Result of analysis that does in this research find that in partially has significant effect of organization culture and employee’s satisfaction to the performance staff in University of Mercu Buana Jakarta. Suchwith in simultanously also find significant effect of organization culture and employee’s satisfaction to thestaff performance in University of Mercu Buana Jakarta.